The impact of language environment and learning motivation on English learning outcomes in Indonesian Islamic university - Andi Nurwati; Gusnawaty Gusnawaty (JEELS (Journal of English Education and Linguistics Studies), 2025)
In response to the growing demand for transformative English education in Islamic higher education, this study investigates the interplay among language environment, school background, and learning motivation in shaping English learning outcomes in Islamic higher education. Employing a quantitative research design with path analysis, the study examines both the direct and indirect effects of these variables on students’ English proficiency. Data were collected from 77 undergraduate students at State Islamic Institution of Sultan Amai Gorontalo through objective English proficiency tests and structured questionnaires. The findings reveal that learning motivation plays a pivotal mediating role, accounting for 27.98% of the variance in English learning outcomes. Although the language environment exerts a significant indirect effect through motivation (1.60%), its direct influence on learning outcomes is minimal (0.31%). Likewise, school background shows no significant direct effect on English achievement, suggesting a “transitional reset effect” as students adjust to the higher education context. These results challenge traditional assumptions regarding the roles of prior schooling and learning environment, emphasizing motivation as a central factor in English learning. The study contributes to second language acquisition theory by integrating institutional and psychological perspectives within Islamic higher education and highlights the need for motivation-driven, culturally responsive instructional strategies.